Case reportUncontrolled human papilloma virus infection in a 28-year-old man leading to death – case report and review of literature - Szybiak, Bartosz; Marszałek, Andrzej; Łuczewski, Łukasz; Golusiński, Paweł; Pazdrowski, Jakub; Majchrzak, Ewa; Pieńkowski, Piotr; Golusiński, Wojciech (Polish Journal of Pathology, 2015)
Recurrent respiratory papillomatosis is an increasingly common disease which leads to organic and functional limitations. Clinical symptoms depend on the location and extent of the papillomatosis. They include hoarseness, cough, and, in some cases, significant narrowing of the respiratory and digestive tracts. The present report describes a fatal case of a young man (28 years old) who developed a very dynamic papilloma infection of the larynx, which spread to the trachea, the oesophagus, the soft tissues of the neck, and the mediastinum. Multimodal treatment did not stop the progression of the disease. The papillomatous lesion was removed with a CO 2 laser used in a Kleinsasser microlaryngoscopy and under a microscope using a electrocoagulation loop with argon plasma during the gastroscopy. Antiviral treatment with cidofovir was introduced, as well as in further follow-up radiotherapy. Congenital or acquired immunodeficiency was also excluded. Despite multimodal treatment, successful eradication of the infection was not possible. In our case, aggressive progression of the disease was observed. We were unable to confirm malignant transformation. Papillomatosis was the only disease, and its aggressive development led to the patient’s death. In the case of aggressive, uncontrolled progression – when the infiltration spreads beyond the larynx and the hypopharynx – there are no alternative treatment methods that would lead to an effective cure.